Проблема застосування рекомендаційних алгоритмів для консультування у туристичній галузі - Полянська, Анастасія; Левус, Євгенія (Видавництво Львівської політехніки, 2020)
This paper tells about the current state of usage of recommendation algorithms in tourism consulting, specialties and problems of this sphere. It states why well known methods of consulting are not perfect for this task and what can be improved based on existing recommendation algorithms and previous knowledge.
Keywords: рекомендаційні алгоритми; колаборативна фільтрація; туристична галузь